At the islands, Trinidad, B.W.I. - (:unkn) unknown (My University, 2011)
This postcard shows a small island, which is one of the group of "Five Islands” which are actually six islands located west of Port of Spain in the Gulf of Paria. The islands are Pelican, Caledonia, Craig, Nelson, Lenagan, Rock Islands.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); Five Islands, The